KULTUR PEMBELAJARAN GURU PKn SMP NEGERI DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Tuti Oktafiani; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out how the learning culture of State JuniorHigh School Civics teachers in Singingi District, Kuantan Singingi Regency. As for thepopulation and sample in this study are all of the State Junior High School Civicsteachers in Singingi District, Kuantan Singingi Regency were 12 people. By using totalsampling technique.. Data collection techniques used are through observation,questionnaires, interviews and documentation. In analyzing the data using quantitativedescriptive methods. The results of this study indicate that the learning culture of StateJunior High School Civics Teachers in Singingi Subdistrict, Kuantan Singingi Regencyruns very well. This is evidenced by the data from respondents that 21.73% answered"Very Good", 72.48% answered "Good", 4.34% answered "Good enough" and 0.36%answered "Not Good". Based on the benchmark proposed by Suharsimi Arikunto(2010), the number of respondents who answered very well + good was 94.21% in therange of 75,01%-100% or very good. It is expected that with this research the teachercan maintain and also improve the culture of learning by innovating better and moreinteresting to support the students' learning spirit in the classroom.Key Words: Learning Culture, PKn teacher